2010
DOI: 10.1097/fjc.0b013e3181f68209
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Proton Pump Inhibitors on the Antiplatelet Potency of Clopidogrel Evaluated by 5 Different Platelet Function Tests

Abstract: Proton pump inhibitors (PPIs) are metabolized by the cytochrome P450 enzyme system to a variable degree and may therefore interact with the metabolism of clopidogrel to its active form. The conflicting data on this potential interaction may be due to the use of different PPIs and platelet function tests in recent studies. We therefore evaluated the influence of different PPIs on the antiplatelet effect of clopidogrel by 5 platelet function tests in the same population. Adenosine diphosphate (ADP)-inducible pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…Notably, PPIs differ in their ability to inhibit CYP2C19, omeprazole being a more potent inhibitor than the other members of the class [17,18] . Accordingly, some studies showed that omeprazole attenuates the antiplatelet effect of clopidogrel [13][14][15] but others did not confirm these findings [19,20] . In contrast, esomeprazole, lansoprazole, pantoprazole and rabeprazole did not affect platelet function in patients treated with clopidogrel [13,15,[19][20][21][22] .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Notably, PPIs differ in their ability to inhibit CYP2C19, omeprazole being a more potent inhibitor than the other members of the class [17,18] . Accordingly, some studies showed that omeprazole attenuates the antiplatelet effect of clopidogrel [13][14][15] but others did not confirm these findings [19,20] . In contrast, esomeprazole, lansoprazole, pantoprazole and rabeprazole did not affect platelet function in patients treated with clopidogrel [13,15,[19][20][21][22] .…”
Section: Introductionmentioning
confidence: 93%
“…Accordingly, some studies showed that omeprazole attenuates the antiplatelet effect of clopidogrel [13][14][15] but others did not confirm these findings [19,20] . In contrast, esomeprazole, lansoprazole, pantoprazole and rabeprazole did not affect platelet function in patients treated with clopidogrel [13,15,[19][20][21][22] . However, it is unclear whether these ex vivo findings have clinical importance, i.e., if the co-administration of clopidogrel with omeprazole or other PPIs will result in reduced protection against cardiovascular events.…”
Section: Introductionmentioning
confidence: 93%
“…22,33,35 Three studies performed head-to-head comparisons between different PPIs (Table 2); none found any significant differences. 35,37,46 Five studies 32,34,41,44,45 reported subgroup analyses for platelet outcomes with different PPIs. Generally, no effect was found for pantoprazole, an effect was demonstrated for omeprazole, and findings with esomeprazole were equivocal.…”
Section: Interaction Between Ppis and Clopidogrelmentioning
confidence: 99%
“…1,6,22, This has usually been assessed by the platelet reactivity index vasoactive-stimulated phosphoprotein or the adenosine diphosphate-induced platelet aggregometry. 35,45,[52][53][54][55][56] Nineteen studies have found that PPI use was associated with a statistically significant reduction of the antiplatelet activity of clopidogrel, 1,6,22,30,33,34,36,[40][41][42][43][44][45][46][47][48][49][50][51] whereas 4 35,[37][38][39] found no effect. Three studies found that dose separation between clopidogrel and the PPI did not prevent the pharmacokinetic interaction and did not alter the influence on antiplatelet effect.…”
Section: Interaction Between Ppis and Clopidogrelmentioning
confidence: 99%
“…Omeprazol ile gösterilen bu ilaç etkileşimi diğer bazı PPI'larda (pantoprazol ve esomeprazol) çok daha az belirgindir. Bunun nedeni bu PPI'ların CYP2CA9'u daha az oranda etkilemesidir (12,13) . Öbür yandan PRINCIPLE-TIMI 44 çalışmasının post-hoc analiz sonuçlarına göre klopidogrel kullanımı ile birlikte herhangi bir PPI kullanımı sonrası azalmış platelet inhibisyonu izlenmiştir (14) .…”
Section: öZetunclassified